A Transdisciplinary Approach: The Picture of Dorian Gray from the Viewpoint of Physics - Huguenin, José A.O.; Wolkoff, Gisele G (ABEI Journal, 2017)
As we wander around universal literature and some central ideas in Physics, we present a transdisciplinary reading of the novel The Picture of Dorian Gray, by Oscar Wilde, and Quantum Mechanics, thus, pointing out to the importance of inter and transdisciplinary looks into contemporary studies in diverse areas of knowledge.